Phosphorus solubilization in the Composting process (Research, Society and Development, 2026)
Phosphorus (P) has low availability in tropical soils due to strong mineral adsorption. This study aimed to evaluate the solubilization of P during the composting of organic waste associated with reactive natural phosphate FosBio®. The experiment was conducted in Machado, MG, for 60 days, under a randomized block design with six treatments composed of bovine manure, coffee straw, and sawdust, with and without the addition of FosBio®. The contents of total P and its fractions soluble in water, neutral ammonium citrate (NAC + water), and 2% citric acid were analyzed. The inclusion of FosBio® significantly increased soluble P, with the Manure + FosBio® treatment standing out, achieving the highest average solubility (1.68 in citric acid). Waste with a high C/N ratio, such as sawdust, limited solubilization due to microbial immobilization, while coffee straw favored the maintenance of available P. It is concluded that the association between bovine manure and FosBio® with residues of lower C/N ratio is a sustainable alternative for the production of organomineral fertilizers and the building of soil fertility.